Temporal trends in optimal diabetic care and complications of elderly type 2 diabetes patients in Thailand: A nationwide study. Issue 1 (5th November 2018) - Kaewput, Wisit; Thongprayoon, Charat; Mungthin, Mathirut; Jindarat, Sarawut; Varothai, Narittaya; Suwannahitatorn, Picha; Rangsin, Ram; Mao, Michael A; Cheungpasitporn, Wisit
Abstract: Background: This study aimed to assess the nationwide trends in optimal diabetic care and complications of elderly type 2 diabetes mellitus (T2DM) patients over a 6‐year period in Thailand. Methods: T2DM patients aged 65 years or older who received medical care at public hospitals in Thailand from 2010 to 2015 were included. The optimal T2DM care in elderly patients was defined as (1) blood pressure (BP) < 140/90, (2) hemoglobin A1C (HbA1c) < 7%, (3) low‐density lipoprotein cholesterol (LDL‐C) < 100 mg/dL, (4) use of antiplatelet medications, and (5) use of angiotensin‐converting enzyme inhibitors (ACEIs) or angiotensin II receptor blockers (ARBs) in hypertensive patients. T2DM treatment‐related complications included hospital admissions due to dysglycemia. Results: A total of 54 295 elderly T2DM patients were enrolled in this study. From 2010 to 2015, there was an increasing trend in the achievement of BP control and use of antiplatelet medications ( P for trend < 0.01), whereas there was a decreasing trend in the achievement of HbA1c and LDL‐C control among elderly T2DM patients ( P for trend < 0.001). There was an increasing trend in the use of ACEI/ARB among elderly T2DM patients with hypertension ( P for trend < 0.001). Hospital admissions due to dysglycemia decreased over the study period ( P for trend < 0.001). Conclusion: There has been a trend change for diabetic care among elderly T2DM patients in Thailand. Further studies are needed to assess the impact on patient outcomes.